Evaluating environment radiations at Axesse linac undergoing NPC treatment of VMAT. (16th December 2016) - Chen, L. F.; Tseng, H. C.; Pan, L. K.; Lin, J. B.; Huang, H. S.; Lai, W. H.; Chen, C. Y.
Abstract: Environment radiations in vault rooms resulting from Axesse linac use was assessed at Medical University Hospital using Thermoluminescent dosimeters (TLDs) during the use of the new radiation treatment known as volumetric modulated arc therapy (VMAT) in the treatment of nasopharyngeal cancer (NPC). The TLD-100H was calibrated using linac 6 MV photons. A total of 75 measurement points of the TLD-100H were utilized for environmental monitoring. The measured environment radiations were then visualized as three-dimensional graphical representations. Environment radiations were visualized using colored three-dimentional graphical representations. The radiations in NPC treatment of Rando phantom was found to reach levels up to 370 mSv/treatment. Many researchers consider TLD, which is the most cost-effective method to environment radiations. The minimum detectable dose (MDD) was also identified to demonstrate the reliability of the TLD approach. Quantitative results that provide practical guidance with regarded radiation protections. Potentially hazardous of secondary radiations from the operating linac is evaluated with regard to its potential health effects on both patients and the public. KEY POINTS: This work tried to evaluate the environment radiation and minimal detectable limit of TLD inside the LINAC maze.